Healthcare‐associated blood stream infections in hematological patients in Finland during the years 2006‐2016. (22nd June 2021) - Åttman, Emilia; Syrjänen, Jaana; Lyytikäinen, Outi; Ollgren, Jukka; Sinisalo, Marjatta; Vuento, Risto; Mattila, Erja; Huttunen, Reetta
Abstract: Objectives: The aim was to identify the clinical characteristics, outcome, and antimicrobial susceptibility of healthcare‐associated bloodstream infections (BSIs) in hematological patients. Methods: This retrospectively collected laboratory‐based surveillance data include 3404 healthcare‐associated BSIs in 2296 patients with a hematological malignancy in hospitals participating in the Finnish Hospital Infection Program from January 1, 2006, to December 31, 2016. Results: The most common underlying diseases were acute myelogenous leukemia (35%) and non‐Hodgkin lymphoma (22%). Gram‐positive organisms accounted for 60%‐46% and gram‐negative organisms for 24%‐36% of BSIs in 2006‐2016. The most common causative organism was coagulase‐negative staphylococci (CoNS) (n = 731). The 7‐ and 28‐day case fatality rates were 5.2% and 11.4%, respectively, and was highest in BSIs caused by Candida species (10.8% and 30.8%). The median age of patients increased from 59 years in 2006‐2008 to 62 years in 2015‐2016 ( P < .01). Five percent of S aureus isolates were resistant to methicillin and five percent of Pseudomonas aeruginosa isolates were multidrug‐resistant. Four percent of Klebsiella and seven percent of E coli isolates were resistant to ceftazidime. Conclusions: The proportion of gram‐positive bacteria decreased and gram‐negative bacteria increased over time. The case fatality rate was low and the median age of patients increased during the study.